2007
DOI: 10.1063/1.2750384
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear instability of a thin film flowing down a smoothly deformed surface

Abstract: Here, the nonlinear flow instability of a thin film flowing down an inclined wall with smooth deformations is investigated. A nonlinear evolution equation is obtained under the small wavenumber approximation. This equation describes the film free surface deformation including the effects of inertia, viscosity, surface tension, and deformation of the wall. The equation has a forcing term that corresponds to periodic time-dependent perturbations hitting on the free surface. These time-dependent perturbations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
58
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 44 publications
1
58
0
Order By: Relevance
“…Recent experiments, however, in which the flow is taken to be essentially two-dimensional in a streamwise cross-sectional plane, have demonstrated that there is a strong coupling between inertia and topography for the case of gravity-driven flow over surfaces containing spanwise periodic rectangular ; Argyriadi, Vlachogiannis and Bontozoglou, 2006) or wavy (Wierschem, Lepski and Aksel, 2005) features. The experimentally-observed rise in critical Reynolds number with increasing topography steepness that occurs has also been predicted theoretically by several authors, see for example , Trifonov (2007) and Dávalos-Orozco (2007; conversely, it has been reported recently that undulating surfaces may have a destabilising influence on the flow if the surface tension is sufficiently high (Heining and The present work has two main strands in relation to gravity-driven film flow at finite Reynolds number in the presence of an electric field normal to it: two-dimensional flow over dis-crete steep and smooth periodically varying spanwise topography revisited; three-dimensional flow over localised steep topography, the exploration of which is considered for the first time. In both cases, the hydrodynamics is modelled using the approach of Veremieiev et al (2010) and the governing equation set solved numerically.…”
mentioning
confidence: 66%
“…Recent experiments, however, in which the flow is taken to be essentially two-dimensional in a streamwise cross-sectional plane, have demonstrated that there is a strong coupling between inertia and topography for the case of gravity-driven flow over surfaces containing spanwise periodic rectangular ; Argyriadi, Vlachogiannis and Bontozoglou, 2006) or wavy (Wierschem, Lepski and Aksel, 2005) features. The experimentally-observed rise in critical Reynolds number with increasing topography steepness that occurs has also been predicted theoretically by several authors, see for example , Trifonov (2007) and Dávalos-Orozco (2007; conversely, it has been reported recently that undulating surfaces may have a destabilising influence on the flow if the surface tension is sufficiently high (Heining and The present work has two main strands in relation to gravity-driven film flow at finite Reynolds number in the presence of an electric field normal to it: two-dimensional flow over dis-crete steep and smooth periodically varying spanwise topography revisited; three-dimensional flow over localised steep topography, the exploration of which is considered for the first time. In both cases, the hydrodynamics is modelled using the approach of Veremieiev et al (2010) and the governing equation set solved numerically.…”
mentioning
confidence: 66%
“…The influence of the time dependent perturbations has been investigated in (Dávalos-Orozco et al 1997) where the impact of the frequency of the perturbation and the magnitude of the Reynolds number on the free surface pattern were made clear. Smooth spatial wall deformations were investigated in (Dávalos-Orozco 2007). In that paper, a review is given of papers which present results related with this problem but under different approximations.…”
Section: Introductionmentioning
confidence: 98%
“…Functions that satisfy this condition are the sine and cosine. In (Dávalos-Orozco 2007) it was shown that in the case of a sinusoidal wall it is possible to stabilize the time dependent perturbations propagating on the free surface response to the wall. However, in that case, the wall had sinusoidal deformations with infinite extension.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations